2021
DOI: 10.1101/2021.08.06.455481
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporally Auto-Correlated Predator Attacks Structure Ecological Communities

Abstract: For species regulated by a common predator, the P* rule predicts that the prey species that supports the highest mean predator density (P*) excludes the other prey species. This prediction is re-examined in the presence of temporal fluctuations in the vital rates of the interacting species including predator attack rates. When the fluctuations in predator attack rates are temporally uncorrelated, the P* rule still holds even when the other vital rates are temporally auto-correlated. However, when temporal auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…For example, alternative stable states are driven by positive frequency dependence, while coexistence is driven by negative frequency dependence (Ke & Letten, 2018; Schreiber et al ., 2019; Mordecai, 2011). Similarly, Schreiber (2021, 2022) discuss the possibility of negative storage effects, which would not contribute to coexistence but rather hamper it. More generally, in a meta-analysis of niche and fitness differences across different ecological communities Buche et al (2022) found that niche differences of coexisting species-pairs differ qualitatively from niche differences of competitively excluded species, independent of whether these were driven by positive or negative frequency dependence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, alternative stable states are driven by positive frequency dependence, while coexistence is driven by negative frequency dependence (Ke & Letten, 2018; Schreiber et al ., 2019; Mordecai, 2011). Similarly, Schreiber (2021, 2022) discuss the possibility of negative storage effects, which would not contribute to coexistence but rather hamper it. More generally, in a meta-analysis of niche and fitness differences across different ecological communities Buche et al (2022) found that niche differences of coexisting species-pairs differ qualitatively from niche differences of competitively excluded species, independent of whether these were driven by positive or negative frequency dependence.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal storage effect can also be mediated through predation, but only if predation changes concomitantly with the the the environmental parameter. This can happen through temporal autocorrelation in the predator's demographic rates (Schreiber, 2021a), or if predators exhibit behavioral responses to changes in prey density . Prey species can experience a negative temporal storage effect (undermining coexistence) if their predators have type 2 functional responses (Stump, 2017), such that residents can satiate their predators but invader cannot.…”
Section: ∆N I : Relative Nonlinearitymentioning
confidence: 99%
“…If positive, the coexistence mechanism generally uplifts all species. If negative, the mechanism is generally destabilizing; in models without allee effects, mutualisms, or knock-on extinctions, a negative community-average coexistence mechanism is evidence of priority effects, which are classically presented in a Lotka-Volterra framework (Amarasekare, 2012), but may be mediated through fluctuation-dependent coexistence mechanisms (Chesson, 1988;Schreiber, 2021b;Schreiber, 2021a).…”
Section: Community-average Coexistence Mechanismsmentioning
confidence: 99%